On the Sensitivity of Semisimple Multiple Eigenvalues (Journal of Computational Mathematics, 1992)
This paper is a supplement to the work in [6] where we investigated the directional derivatives of semisimple multiple eigenvalues of a complex $n× n$ matrix analytically dependent on several parameters. The result of this paper can be used to define the sensitivity of semisimple multiple eigenvalues in a more reasonable way than in [6].